Formal [3+2] cycloaddition of vinylcyclopropane azlactones to enals using synergistic catalysis - Kamlar, Martin; Franc, Michael; Císařová, Ivana; Gyepes, Róbert; Veselý, Jan (Chemical communications (Cambridge, England), 2019)
The present study reports the asymmetric cyclization of enals with vinylcyclopropane azlactones efficiently catalyzed by the combination of achiral Pd(0) complexes and chiral secondary amines. Corresponding spirocyclic azlactones were produced in high yields with moderate diastereoselectivities and excellent enantioselectivities. This protocol provides an efficient and easily-performed route to spirocyclic scaffolds, and densely functionalized cyclopentanes containing quaternary carbon centers.